Estudo da ecologia química da broca-do-fruto do Cupuaçuzeiro Conotrachelus humeropictus Fiedler, 1940 (Coleoptera: Curculionidae): prospecção de semioquímicos e estudos comportamentais - (:unkn) unknown (Universidade Federal do Amazonas, 2018)
This thesis had the objective the prospection of semiochemicals and behavioral studies of cupuassu fruit borer (Conotrachelus humeropictus Fiedler, 1940). In this study, worked on perspective of understand, origin, function and meaning of the natural chemical compounds that regulate the interactions between C. humeropictus and the cupuassu ((Theobroma grandiflorum (Willd. Ex Spreng) Schum), in this case, including pheromones and allelochemicals. For this, studies with semiochemical of the insects and plants were developed in cupuassu plantations located in the experimental fields of Embrapa Western Amazonia, in the region of Manaus-Amazonas between the years of 2015 and 2017. The chemical analyzes of cupuassu aeration extracts showed that there is difference in the composition of the volatile mixtures released at the phenological stages considered. The class of compounds released in the different stages was similar being composed mainly of monoterpenes, sesquiterpenos and some aromatics. Adult males of C. humeropictus responded preferentially to odors released by the cupuassu in the phenological stages of fructification. The chemical analysis of aeration extracts of males and females showed that males produce three specific compounds that are not present in the aeration extracts of females, the compounds grandisoic acid, grandlure I and grandlure II. Male volatiles are attractive to females and females also respond to the grandiose acid majoritarian compound. The survey and monitoring of adults in the orchard used in this study found a higher level of insect infestation in plants located around the forest, where approximately 91% of adult insects were also present. The level of infestation during the harvest reached 42%, with an average of four borer per fruit. Adults of C. humeropictus were collected in all months of the year, with lower levels than during the harvest period. These results have important implications for the use of semiochemicals in the integrated pest management of cupuassu.
Keywords: Feromônio; Broca-do-cupuaçu; Compostos orgânicos voláteis; Cupuaçu; CIÊNCIAS AGRÁRIAS: AGRONOMIA